Will Innovation of Pharmaceutical Manufacturing Improve Perceived Health? - Li, Zejun; Li, Xue (Frontiers in Public Health, 2021)
By taking 22 OECD countries from 2010 to 2017 as sample, we study the effect of pharmaceutical manufacturing innovation on perceived health by using panel Tobit model from a whole and sub-samples respectively, as well as analyzes their transmission channels by adding moderating effect. Based on the above, we get the following results: first, the pharmaceutical manufacturing innovation four years ago has a positive influence on perceived health, which means the improvement of perceived health is closely related to pharmaceutical manufacturing innovation four years ago. Second, pharmaceutical manufacturing innovation has a heterogeneous impact on perceived health, which including the size and direction of the impact effect, are mainly reflected in different pharmaceutical manufacturing innovation level, population aging degree and education level. Third, income level can positively regulate the impact of pharmaceutical manufacturing innovation on perceived health.